Reproduction and recruitment dynamics of flathead chub Platygobio gracilis relative to flow and temperature regimes in Fountain Creek, Colorado - Haworth, Matthew R., author; Bestgen, Kevin R., advisor; Fausch, Kurt D., committee member; Bledsoe, Brian P., committee member (Colorado State University. Libraries, 2015)
A paucity of basic ecological information for flathead chub Platygobio gracilis has made effective conservation planning difficult for this declining species. The objective of this study was to contribute insight to the poorly understood reproductive ecology of flathead chub, and enable prediction of effects of future hydrologic alterations in Fountain Creek, Colorado, to avoid or mitigate negative impacts from these actions. To accomplish this I investigated the influence of flow and water temperature regimes on reproduction and recruitment dynamics of flathead chub in Fountain Creek from May 2012 to October 2013 through collection of eggs, and analysis of otoliths from larvae and juveniles. Presence of flathead chub eggs and larvae in drift nets and Moore egg collectors indicated a protracted spawning season spanning a four-month period from mid-May to mid-September. Species composition of fish hatched from eggs reared in the laboratory showed the majority of eggs captured in drift nets were flathead chub. This enabled identification of peak reproduction periods based on captures of eggs in preserved samples. Reproduction began in each year when water temperatures exceeded 15°C, and highest egg densities occurred in later May and June in both 2012 and 2013. Unlike literature suggestions of need for flow spikes to induce reproduction, spawning occurred during both steady low flow conditions and to a lesser extent, under fluctuating flows caused by convective storms. Larvae hatching also peaked in May and June but, unlike egg production, was restricted to periods of stable low flows of about 1-2 m³/s. Recruitment, in this study defined as the addition of an individual to the population by survival to the juvenile stage, occurred only in a subset of the egg production season during periods of low and steady flows, usually in late May and June. In contrast, egg production preceding or during flow spikes that reached approximately 20 m³/s produced few recruits, presumably because eggs and weak-swimming larvae were transported downstream or destroyed. Recruitment sometimes occurred prior to flow spikes, but the minimum duration of relatively steady flows required was about three weeks. Both episodic and frequent high magnitude flow events had large and negative impacts on recruitment of flathead chub, and potentially population dynamics of the species in Fountain Creek. This is mostly counter to the prevailing paradigm that high flows are required for many plains-adapted minnow species to reproduce, a hypothesis formulated mostly from observations in flow-depleted streams where such patterns may be an artifact of an altered environment. This study was successful in identifying environmental conditions suitable for flathead chub reproduction and recruitment related to temperature and flow regimes in Fountain Creek. Managers should use these insights to predict how future hydrologic alterations may affect the flathead chubs so the population in Fountain Creek can be conserved.